2012
DOI: 10.1039/c2cp41137g
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical study of spiropyran–terthiophene derivatives: photochemistry and thermodynamics

Abstract: The photochemistry and thermodynamics of two terthiophene (TTh) derivatives bearing benzospiropyran (BSP) moieties, 1-(3,3''-dimethylindoline-6'-nitrobenzospiropyranyl)-2-ethyl 4,4''-didecyloxy-2,2':5',2''-terthiophene-30-acetate (BSP-2) and 1-(3,3''-dimethylindoline-6'-nitrobenzospiropyranyl)-2-ethyl 4,4''-didecyloxy-2,2':5',2''-terthiophene-30-carboxylate (BSP-3), differing only by a single methylene spacer unit, have been studied. The kinetics of photogeneration of the equivalent merocyanine (MC) isomers (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…It also indicated that the SP−C[4]A tetra‐ureas may be degraded (not photo‐stable) under the long irradiation conditions used to achieve the PSS. [46] We obtained similar results using the calix[4]pyrrole counterpart all‐SP−C[4]P (Figure S19).…”
Section: Resultssupporting
confidence: 62%
“…It also indicated that the SP−C[4]A tetra‐ureas may be degraded (not photo‐stable) under the long irradiation conditions used to achieve the PSS. [46] We obtained similar results using the calix[4]pyrrole counterpart all‐SP−C[4]P (Figure S19).…”
Section: Resultssupporting
confidence: 62%
“…[12][13][14] In the case of T-type photochromes, this feature is important and exciting because it allows to control the stability of the photoinduced form by changing the temperature conditions. This issue has been well studied for known groups of photochromes, such as spiropyrans, 15,16 spirooxazines, 17 azobenzenes, 18,19 diarylethenes, 20,21 dihydropyrene, 22 dihydroindolizines 23 and bindone derivatives. 24 Papers [15][16][17][18][19][20][21][22][23][24] also demonstrate that the analysis of the temperature effect on the rate constant allows to estimate various important energy parameters of the reverse thermal reaction of photochromes, for example activation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Various trimer carboxylic acids have been prepared, directly connected to the thiophene rings [ 342 , 343 , 344 , 345 ] or linked through a spacer. In fact, spacers of one [ 346 , 347 , 348 , 349 , 350 , 351 , 352 ], two [ 279 , 353 , 354 ], three [ 355 ], four [ 354 ], five [ 356 ] or six [ 350 ] carbon atoms are reported ( Scheme 18 , I and II).…”
Section: Trimer Structuresmentioning
confidence: 99%
“…The negative charge of carboxylic acid is widely exploited for promoting attractive interactions between the trimer and other molecules, materials or surfaces [ 349 , 350 , 355 , 358 , 359 ]. Additionally, trimers carrying a carboxylic acid can be easily functionalized by esterification or amidation [ 343 , 346 , 347 , 360 ].…”
Section: Trimer Structuresmentioning
confidence: 99%
See 1 more Smart Citation